2011
DOI: 10.20452/pamw.1093
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in endothelial cell pathophysiology

Abstract: MicroRNAs (miRNAs) are a family of small, noncoding RNAs that repress gene expression at the post-transcriptional level. Over 700 miRNAs have been identified in the human genome, of which 20% to 30% regulate human protein-coding genes. Functional in vitro studies have shown that miRNAs are critical for endothelial cell gene expression and function. miRNAs were found in atherosclerosis, cardiac hypertrophy, arterial hypertension, coronary artery disease, diabetes, and inflammatory diseases. We review the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 51 publications
4
67
1
5
Order By: Relevance
“…Expression of miR155 was also detected in endothelial cells. In line with this, miR155 expression in blood vessels has been reported in GG (Prabowo et al, 2015) and this miRNA has been shown to be implicated in endothelial cell functions and angiogenesis (Kong et al, 2014;Lopez-Ramirez et al, 2014;Staszel et al, 2011;Wu et al, 2014). The positive correlation observed between miR21, miR146a, and miR155 and the expression of GFAP in tubers supports the role of astrocytes as source and targets of regulation of these miRNAs.…”
Section: Inflammation-related Micrornas In Tsc Brain Lesionssupporting
confidence: 64%
“…Expression of miR155 was also detected in endothelial cells. In line with this, miR155 expression in blood vessels has been reported in GG (Prabowo et al, 2015) and this miRNA has been shown to be implicated in endothelial cell functions and angiogenesis (Kong et al, 2014;Lopez-Ramirez et al, 2014;Staszel et al, 2011;Wu et al, 2014). The positive correlation observed between miR21, miR146a, and miR155 and the expression of GFAP in tubers supports the role of astrocytes as source and targets of regulation of these miRNAs.…”
Section: Inflammation-related Micrornas In Tsc Brain Lesionssupporting
confidence: 64%
“…We believe that changes observed in the levels of miR-433 in response to variations in the redox state are specific. As shown in Supplementary Figure S6, both the redoximir miR-34a (61,64) and the fibromir miR-21 (49,51) behave similarly to miR-433 when exposed to BSO. However, when Nrf2 was silenced, miR-34a and miR-21 exhibited a tendency to increase.…”
Section: Discussionmentioning
confidence: 84%
“…Both miR-34a and miR-217 promote, whereas miR-146a quells endothelial cell senescence (Qin et al 2012;Menghini et al 2013). miR-34a is highly expressed in endothelial cells and the degree of expression increases during cell senescence (Ito et al 2010;Staszel et al 2011;Menghini et al 2013). miR-34a targets and downregulates sirtuin-1 (SIRT1), a major regulator of endothelial cell longevity and metabolic function (Potente and Dimmeler 2008;Ito et al 2010;Zhao et al 2010).…”
Section: Discussionmentioning
confidence: 99%